Makna Serangan Fajar pada Pemilu: Kajian Sosiologi Politik dalam Pesta Demokrasi Indonesia - Maifizar, Arfriani; Ogam, Muhammad Jodi; Handayani, Tri Quari (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Dawn attack is a term often used in the world of Indonesian politics to describe the practice of money politics that occurs ahead of election day. This phenomenon involves giving money or goods to voters with the aim of influencing their vote. This article discusses the origin of the term dawn attack, the mechanism for its implementation, and its impact on the integrity of the electoral process in Indonesia. In addition, this article also explores the efforts that have been made to address the practice of dawn raids and the challenges faced in their implementation. Through this analysis, it is hoped that it can provide a deeper understanding of the dawn attack phenomenon and the guarantee of democracy in Indonesia.